Challenging the hegemony of English in African education and literature: The case of Zimbabwe - Charamba, Tyanai; Mutasa, Davie E. (NISC (Pty) Ltd and Routledge, 2016)
The struggle against the hegemony of English in the education system and literary practice in Africa became vigorous from the late 1950s and the early 1960s when the British colonies of Africa began to attain political independence. This article uses Zimbabwean university education and literary practice to discuss the approaches which have so far been used by African people in that struggle. The effectiveness of those approaches are considered using different scholarly research findings and drawing examples from what happened and/or is still happening in Zimbabwe and relating it to what is happening in other African and non-African countries. Furthermore, the article explores the effectiveness of those approaches from an understanding that the hegemony of the English language is closely linked to superpower politics in general. Superpower politics has a direct and an indirect influence on the manner in which Zimbabweans and Africans in general choose languages of university education and literary creation. The article concludes that, as long as world politics is superpower politics, and as long as the superpower is an English-speaking nation, the hegemony of English will remain a force to be reckoned with in Zimbabwe’s university education and literary practice.